Occult Cervical Avulsion: A Rare Cause of Intrapartum Vaginal Bleeding - Charity Hulin; Brennan Lang; Jennifer Stanley; Christina Davidson (Case Reports in Obstetrics and Gynecology)
Background. Cervical avulsion, complete or partial, is a rare intrapartum complication that can go unrecognized without proper physician vigilance. Cases. Case 1 is a 32-year-old multiparous woman admitted for induction of labor at 37 2/7 weeks for abnormal antenatal testing. Case 2 is a 22-year-old multiparous woman at 29 0/7 with spontaneous preterm labor 10 days after cerclage removal for preterm contractions. Vaginal bleeding and fetal heart rate decelerations complicated each patient’s intrapartum course. Annular cervical detachment noted at time of delivery resulted in partial or complete amputation of the cervix. Both women recovered well postpartum. Conclusion. This rare phenomenon should be considered in the differential of intrapartum vaginal bleeding to avoid a missed or delayed diagnosis.